Development of PICTIONARY GAME Media as a Support for Learning Chinese Vocabulary Class XI BBD SMA Kristen 1 Salatiga - Christiani, Atalya Filadelfia; Pamuji, Dian Yuni; Marsuki, Ria Riski; Agwinanda, Almira (Universitas Negeri Makassar, 2025)
The objectives of this study were to 1) describe the results of the needs analysis of the Pictionary game media as a Chinese vocabulary learning aid for the XI BBD SMA Kristen 1 Salatiga class; 2) describe the prototype of the Pictionary game media as a Chinese vocabulary learning aid for the XI BBD SMA Kristen 1 Salatiga class (2) describe the results of the needs analysis of the Pictionary game media as a Chinese vocabulary learning aid for the XI BBD SMA Kristen 1 Salatiga class; (3) describe the results of the expert validation of the Pictionary game media as a material and media for the XI BBD SMA Kristen 1 Salatiga class. This study utilized a research and development (R&D) methodology divided into several phases, namely 1) potentials and problems; 2) data collection; 3) product design; 4) design validation; and 5) design modification. Based on the results of the needs analysis of students and Chinese language teachers, the development of the Pictionary game media was approved as a supplementary tool for learning Chinese vocabulary. The validation results from the media experts averaged 87.1 points with a score of 4, which is in the very suitable category; the validation results from the textbook experts averaged 88.5 points with a score of 4, which is in the very suitable category. Then, the developed Pictionary game media was improved according to the suggestions made by the experts, i.e., the developed media was good and complete, the media could be tested in the field to make it feel useful, and one vocabulary word in the game card was improved. Keyword: Learning media, vocabulary, hanzi, chinese language, pictionary